Genital herpes - Rogl-Butina, Mirjam (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2000)
Genital herpes is one of the most common sexually transmitted diseases in the world. It results from the infection with herpes simplex virus, commonly with herpes simplex virus type 2, occasionally with type 1. The infection is life-long, and after the initial episode, recurrences can appear any time. Thevirus is able to elicit a number of pathological conditions; however the recurrent clinical outbreaks of genital herpes most often cause not only physical but also psychosocial problems. We present a brief overview of current concepts regarding the epidemiology, pathology, clinical manifestations and treatment options.
Keywords: Diagnosis; epidemiologija; Epidemiology; genitalije; Herpes genitalis; herpes simplex; Herpesvirus 2, human; Therapy; zdravljenje